Comparing Day 0 and Day 21, Hematological and Biochemical Changes on Male White Rattus norvegicus Exposed to Carissa edulis, Water and Ethanolic Extracts, a Herb Commonly used in Management of Diabetes Mellitus in Baringo, County Kenya - Chebor, K.; Osano, O.; Ng’wena, M. (Africa Environmental Review Journal, 2022)
The use of Carissa edulis in the management of Diabetes Mellitus in Baringo County and other parts of Kenya is steadily increasing. This is so, despite the fact that there is a knowledge gap on the Hemato-biochemical responses, on those exposed to it. To investigate the hematological and biochemical changes/responses of Carissa edulis extracts (ethanolic and aqueous) fed to white Rattus norvegicus once daily via oral gavage for 21 days. The study employed an experimental study design. Two kilograms (2 Kg.) of Carissa edulis (CE) roots & back mixtures, were collected from Baringo County, Kenya, where they are commonly used by herbalists in the treatment of diabetes mellitus. They were cleaned at the place of origin, labeled, and transported to the University of Eldoret, Kenya, where its identity was confirmed using their morphological characteristics. Ethanolic and aqueous extraction was done, yield amounts determined and qualitative screening of phytochemicals done. Fifteen (15) male white Rattus norvegicus rats, obtained from the University of Eldoret, Department of biological Sciences were randomly chosen, and caged in 3 cages of 5 rats each. This is after seven (7) days acclimatization, (making the rats adapt the laboratory environment). Sick and rats with abnormalities were excluded in the experiment. Cage 1, 2 and 3, were given orally, ethanolic CE extracts, aqueous CE extracts, and distilled water (controls), respectively. These extracts were given once every day in the morning for 21 days. Blood samples for hematological, (hemoglobin [Hb], red blood cells [RBC], Lymphocytes (LYMPH), Monocytes (MONO), Hematocrit [HCT], Mean Corpuscular Volume [MCV] Mean Corpuscular Hemoglobin [MCH], Mean Corpuscular Hemoglobin Concentration [MCHC] and white blood cells [WBC]) and, biochemical (Urea, creatinine, Alanine Transaminase [ALTs], Aspartate Aminotransferase [ASTs]) tests, were drawn from the rats’ tail end at days 0 and 21. Blood analyzed compared and later the findings presented in figures and in a tabular form. Analysis of the blood was done using using ADVIA 220i for hematology and Chemistry analyzer Cobas C311 for biochemicals. Ethical approval to conduct this study was granted by Animal Research and Ethics Committee (HAREC) of University of Eastern Africa Baraton (UEAB) - Kenya (REC: UEAB/3/1/2018). There was a slight increase in RBC counts, with reference to rats exposed to ethanolic extracted extracts and so to the control groups, but a slight decrease in those exposed to water extracted extracts. Hemoglobin values in both the groups increased (rats exposed to water extracted extracts and rats exposed to ethanolic extracted extracts) but a slight decrease was seen in control groups. With reference to WBC counts, treated animals witnessed a decrease while controls saw an increase. All the tested hematological changes were within the normal ranges. Regarding biochemical parameters tested, in all the rats exposed to the water and ethanolic extracted extracts, their urea levels showed an increase at day 21, while a mixed result was seen in the creatinine parameter – an increase in controls, but a decrease in those exposed to ethanolic extracted extracts and no change was seen those exposed to water extracted extracts. Controls recorded a slight but insignificant drop in ALTs, but an increase in both water and ethanolic extracted extracts. Concerning ASTs, there was a slight increase in controls, a scenario witnessed in both water and ethanolic extracted extracts. The overall changes in all the tested biochemical parameters were also within the normal ranges. Carissa edulis aqueous and ethanolic extracts, given orally to male Wistar albino rats, did not induce any significant interference to the hematological and biochemical parameters, though much more studies in a large scale (use of more rats), at different doses are needed.